Characterization and hepatocytes adhesion of galactosylated poly(D,L-lactic-co-glycolic acid) surface - Choi, Lee; Kwak, Soon Jong; You, Su Jung; Chun, Heung Jae; Kim, Hong Lim; Shim, Young Bock; Kim, Moon Suk; Park, Ki Dong (SPRINGER, 2012)
The present study demonstrated that covalently galactosylated poly(D,L-lactic-co-glycolic acid) (PLGA) surface encourages hepatocyte adhesion and growth to form a dense cell network. Galactosylation of the PLGA surface was accomplished by grafting allylamine (AA) using inductively coupled plasma-assisted chemical vapor deposition (ICP-CVD) and conjugating lactobionic acid (LA) with AA via 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide (EDC/NHS) activation. The modified surface was characterized by Fourier transform infrared spectroscopy in the attenuated total reflectance, electron spectroscopy of chemical analysis, atomic force microscopy, and contact angle measurement. For evaluation of cell affinity in vitro, primary rat hepatocytes were prepared and seeded onto the modified PLGA surfaces. The galactosylated PLGA surface showed more pronounced hepatocyte adhesion and growth compared to those on the control PLGA surface. The hepatocytes seeded on galactosylated substrates exhibited a radial migration with filopodial growth to form multicellular aggregates, whereas those on control PLGA showed slowly adhered rounded shapes. Moreover, galactosylation increased metabolic hepatocyte activities such as albumin secretion and urea synthesis.
Keywords: MODIFIED POLY(DL-LACTIDE-CO-GLYCOLIDE) SCAFFOLDS; HYDROPHILIC MONOMERS; SPHEROID FORMATION; CELLS; IMMOBILIZATION; ATTACHMENT; POLYMER